Penguatan Profil Pelajar Pancasila Melalui Pelatihan Pembuatan Handout Untuk Membangun Nalar Kritis Siswa di lingkungan Perguruan Muhammadiyah Kramatjati, Jakarta Timur - Supriansyah; Ruslan, Ahmad; Syae Purrohman, Purnama; Samiah, Wardah (LPPM Politeknik Piksi Ganesha, 2024)
The profile of Pancasila Students as a translator of the goals and vision of education to a format that is easier to understand by every element in the world of education needs to be considered in every point contained in it, starting from faith and noble character, independence, mutual cooperation, single celebrity, critical and creative reasoning. These six points need to be integrated in learning and non-learning activities. One of the points highlighted is the ability to